Exploring the foundations of tourism geography: between flat ontology and J. Searle’s vertical social ontology - Butowski, Leszek (Bulletin of Geography. Socio-economic Series, 2024)
This article explores the theoretical foundations of tourism geography, focusing on the dialectic between flat ontology and John Searle’s vertical ontology. Drawing from contemporary debates in the field, it examines the philosophical underpinnings of tourism geography and their implications for understanding the social and spatial dynamics of tourism. The concept of flat ontology, rooted in posthuman approach, posits an egalitarian view of the world, where both human and nonhuman entities possess equal ontological status. Proponents argue that this perspective provides a holistic understanding of tourism, acknowledging the co-agency of non-human elements such as landscapes, ecosystems, and material culture. In contrast, J. Searle’s ontology underscores the significance of human intentionality and social structures in shaping the institutional frameworks and practices of tourism. By engaging with these two ontological frameworks, the article highlights the potential synergies, but also tensions between flat ontology and vertical social ontology within tourism geography.